INTERNALISASI MERDEKA BELAJAR DALAM PEMBENTUKAN KARAKTER PROFIL PELAJAR PANCASILA DI ERA SOCIETY 5.0 - Nurul Atikoh; Hidayatul Maslakha; Muhammad Ullin Nuha (FORPIM PTKIS ZONA TAPAL KUDA, 2024)
The era of society 5.0 that we are facing today is also a development of the industrial revolution 4.0 that puts more emphasis on the technological development of every day. The creative abilities of students also influence the creativity of teachers. Educators often simply deliver curriculum materials without encouraging students to show their interests and talents. It inhibits the creativity of the pupils. The aim of this study is to find out the internalization of Merdeka Learning in the formation of the character of the Student Profile of Pancasila in the era of society 5.0. This research method uses a qualitative approach, that is, an approach that produces descriptive data in the form of written words. Reviewed by type, this research is literary, including in the type of library research (library research). Students are given freedom of thought to maximize their knowledge. The result of this investigation is a modern curriculum concept that requires students to study independently, both in formal and non-formal schools. This century's concept of freedom will give students the opportunity to learn as much as possible. Literacy activities enable talent growth through skills and positive things that support the development of each student.